A seesaw‐like mechanism for the neutrino in the presence of a minimal length space–time. Issue 1 (10th January 2023) - Ferreira, Thiago Oliveira; Vasconcellos, César A. Z.; Hadjimichef, Dimiter
Abstract: In the Standard Model, neutrinos appear as left‐handed massless particles, although experimentally they have a tiny, but non‐vanishing, mass. Inspired by quantum gravity, Moayedi, Setare, Moayeri & Poorakbar (2011) used a Lorentz‐covariant algebra for a quantized space–time to derive a modified Dirac equation due to the presence of a minimal length. In this paper, we study this equation in the massless limit in order to describe neutrino states. We show that the minimal length creates a seesaw‐like mechanism that allows us to describe the observed left‐handed neutrinos with vanishing masses while the unobserved right‐handed neutrinos get extremely heavy.